TAXTAQORACHA DOVONI MALAKOFAUNASI - Orziyeva Y, Orziyeva Y; Pazilov A, Pazilov A; Muhammadiyev Z., Muhammadiyev Z. (Actual problems and prospects of the study of the fauna, 2024)
The article found that 18 species of terrestrial molluscs were distributed in the Taxtakaracha pass, studied the density of distribution of 8 species in different biotopes, and found that the population density of Xeropicta candacharica and Candaharia levanderi species was high, revealing its causes.